Deterioration in nutritive value of wheat grains infested with aflatoxigenic strains of Aspergillus flavus - SWETA ROY; A.K. ROY*, AMOD KUMAR, N.L. MANDAL, (Indian Phytopathology, 2013)
Mycotoxin contamination has been reported not only in standing crops or grains under storage but it may also be routed to food products destined for human consumption. Amongst all mycotoxins, aflatoxins are the most significant and widely investigated group which is produced mainly by toxigenic strains of A. flavus and A. parasiticus (8). A. flavus is more ubiquitous in tropical regions; therefore, they easily contaminate different food and feed commodities with aflatoxins. An overview of reports on aflatoxin contamination indicates that practically every edible materials including fruits, vegetables, cereals, pulses, spices and plant drugs too is not spared by moulds contamination and aflatoxin elaboration (7,10) and due to potent hepato-carcinogenic and teratogenic nature of aflatoxins, it derives more attention than any other mycotoxin.